THE USE OF QUESTION ANSWER RELATIONSHIP STRATEGY TO TEACH READING COMPREHENSION OF NARRATIVE TEXTS - Hasanah, Jumia; Sudarsono, Sudarsono; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to examine whether or not Question Answer Relationship (QAR) strategy could affect students’ reading comprehension of narrative texts significantly. This research was a pre-experimental research. The sample of this research was 36 students of class X AK I that was selected by using cluster random sampling. The data were analyzed using non-parametric test in SPSS and the effect size formula. The result of the statistical calculation shows that Wilcoxon Signed-Rank was improved. The value of effect size was 1.5, greater than 0.80 (1.5 > 0.80) and it is categorized highly significant. The research findings show that teaching using Question Answer Relationship (QAR) strategy affected the students’ reading comprehension of narrative texts significantly. It was recommended to use QAR strategy to teach reading comprehension especially on narrative texts.Key words: Question Answer Relationship, Narrative Texts, Pre Experimental